INOVASI PELAYANAN PUBLIK DIGITAL SIPP: ANALISIS PROSES, MAKNA, DAN KEBERLANJUTAN DALAM KERANGKA E-GOVERNANCE KABUPATEN PASAMAN BARAT - Finan Sari Lubis; Aldri Frinaldi; Roberia (Jurnal Manajemen, Ekonomi dan Akutansi (JUMEA), 2026)
Digital transformation in public services is increasingly pressing to improve government efficiency and accountability  (Yusifov  &  Gurbanov,  2024).  This study aims to examine how the digital public service innovation  SiPP  (Training and  Unemployment  Data  Information  System)  in  West  Pasaman  Regency functions in three dimensions:  Process,  Meaning,  and  Sustainability.  Using a qualitative case study design,  data were collected through a triangulation of methods:  in-depth interviews with  Department employees and  Village/Jorong  Wali operators,  direct observation of operational processes,  and analysis of official documentation  (SOPs and system logs).  Key findings indicate that  SiPP is able to reduce data search and compilation time from a full day to  less than  10  minutes and achieves  a  very  high  level  of  user  acceptance  (93.3%  of  respondents  reported  no  problems),  indicating  that  the  system  is  accepted  and  functional  in  daily  bureaucratic  practice.  On  the  sustainability  front,  although  the  system  supports  real-time  data  updates,  internal  regulations  that  mandate  data  updates  only  semiannually  create  an  implementation  gap.  Theoretically,  this  study  extends  the  digital  public  services  literature  by  demonstrating  that  institutional  constraints  can  limit  the  full  potential  of  technology,  not  just  technical  factors  or  user  resistance  (Alshallaqi,  2024).  Practically,  these  results  emphasize  the  importance  of  synchronizing  data  update  frequency  with  system  capabilities  and  cross-sector  needs  so  that  SiPP  can  support  more  responsive  social  and  employment  interventions.